2007
DOI: 10.1002/jssc.200600463
|View full text |Cite
|
Sign up to set email alerts
|

Separation and quantification of 9‐(alkylthio)acridines by capillary micellar electrokinetic chromatography and capillary liquid chromatography

Abstract: Various thioacridine derivatives are potential chemotherapeutics against various diseases which are intensively synthesized, characterized, and investigated by many research groups. Efficient, fast, and reliable separation and quantification methods for their analysis are still to be developed. MEKC and capillary LC (CLC) were applied for the separation and quantification of five highly hydrophobic, weakly basic, and structurally similar 9-(alkylthio)acridines. Since the common anionic and cationic surfactants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In general, the methods reported have been developed in order to determine analytes of clinical and pharmaceutical interest in different samples, and only some of them are worth pointing out. Regarding bile salts, SC micelles have been used for the separation of bioactive licorice compounds 77 (alkyltio)acridines 90 amino acids after derivatization with phanquinone 91 four streoisomers of palonosetron hydrochloride 92, whereas sodium deoxycholate was a useful PSP for the separation of nitrofuran antibiotics 93 and a mixture of herbs commonly present in herbal Chinese formulas 94. Mixed micelles of SC with SDS 95 or another bile salt like taurine 96 have also been reported for the separation of ten flavonoid aglycons belonging to four different classes, and for the determination of shikimate in raw plant extracts, respectively.…”
Section: Approaches For Improving Resolutionmentioning
confidence: 99%
“…In general, the methods reported have been developed in order to determine analytes of clinical and pharmaceutical interest in different samples, and only some of them are worth pointing out. Regarding bile salts, SC micelles have been used for the separation of bioactive licorice compounds 77 (alkyltio)acridines 90 amino acids after derivatization with phanquinone 91 four streoisomers of palonosetron hydrochloride 92, whereas sodium deoxycholate was a useful PSP for the separation of nitrofuran antibiotics 93 and a mixture of herbs commonly present in herbal Chinese formulas 94. Mixed micelles of SC with SDS 95 or another bile salt like taurine 96 have also been reported for the separation of ten flavonoid aglycons belonging to four different classes, and for the determination of shikimate in raw plant extracts, respectively.…”
Section: Approaches For Improving Resolutionmentioning
confidence: 99%
“…The extended application of MEKC in cancer research has been reported in several publications 213, 286–290. MEKC has been used to explore different aspects of cancer research from the search for biological markers in serum, urine, and tissue, to epidemiological studies, to the exploration of anticancer drugs in plant and marine organisms 291.…”
Section: Selected Applicationsmentioning
confidence: 99%